QirÃ¢âah SiyÃ¢qÃ®yah Nasr HÃ¢mid AbÃ» Zayd tentang Hak-hak Wanita dalam al-Qurâan - Billa, Mutamakkin (Mutawatir, 2012)
Starting from the problems that faced by an Egyptian female experts in field of nuclear reactors as well as a lecture at an university who divorced her husband because she refused her husbandâs request for pregnancy/childbirth specially the question of divorce judgment âsuddenlyâ assigned by religious judge based on âcappingâ women role only in domestic region of the family or motherhood (al-ummah). AbÃ» Zayd then analyze the concept of womenâs right in the Koran including its relationship with the polygamy case. At the end of the discussion paper, the authors citing the opinion of AbÃ» Zayd that regard bad argument of supporting of polygamy parties whe base themselves on interpretations and interpretations of fiqh and argued on the basis of the conditions of contemporary morality. That polygamy is the best way, in the sense of itâs smaller dangers than the adultery especially when it is figured on the social-moral in the west